(untitled) (Eurasian Journal of Ecology, 2022)
Titanium and its alloys are widely used in modern supersonic aircraft and rockets, submarines and ships, in the chemical and food industries, as well as in other areas of modern technology. In the process of obtaining titanium from ore, workers may be exposed to titanium metal dust (Ti) and titanium dioxide (TiO 2 ), highly toxic chemical compounds – gaseous titanium tetrachloride (TiC1 4 ), its hydrolysis products, chlorine and phosgene vapors. The study of the influence of titanium produc- tion conditions on the body was carried out at the Ust-Kamenogorsk Titanium and Magnesium Plant (JSC UKTMP) of Kazakhstan, one of the largest enterprises for the production of titanium. To study the behavioral reactions of rodents under the influence of harmful components of the production of magnesium, titanium and their compounds, the «Open field» test was carried out. This test refers to methods that study conditionally unconditioned reflexes. Sexually mature white rats of the Wister line, weighing 180-220 g, were used as a model object; experimental animals were placed on the territory of three main workshops. The motor and emotional behaviors of experimental animals were studied. The assessment of motor activity indicators was determined using such indicators as locomotion and standing, and emotional activity was determined by the number of grooming and boluses (urination and defecation). As a result of the experiment, a unidirectional change in physiological parameters was revealed in animals that were on the territory of JSC «UK TMP» shops, and the quantitative characteristics of physiological processes were different – more pronounced in shop No. 1 (Shop «Magnesium») and less – in shop No. 3 (Shop «Titanium Sponge»). Key words: titanium-magnesium production; experimental animals, physical activity, emotional ac- tivity.